The role of the WspR responce regulator in the adaptive evolution of experimental populations of Pseudomonas Fluorescens SBW25 - Goymer, P; Goymer, Patrick (2002)
﻿ The role of ecological opportunity in adaptive radiation has been demonstrated by the diversification of the bacterium Pseudomonas fluorescens SBW25 in a spatially structured microcosm. This provides an ideal system for studying the genetics of adaptation and asking questions about the genes that matter in evolution. Previous studies have identified the genes that are necessary for the evolved, biofilm-forming, niche-specialist genotype, the wrinkly spreader (WS). These genes are organised in two operons: the wss operon that encodes the genes for cellulose biosynthesis, and the wsp operon that encodes a chemosensory pathway. The terminal gene in the wsp operon, wspR, encodes a novel response regulator thought to regulate the activity of the wss operon. This gene forms the basis of this study, which assesses the role of regulatory genes in adaptive evolution. The structure-function relationship of WspR is established through the phenotypic analysis of overexpressed wspR random point mutants. On this basis a model of WspR activity is proposed which is tested by molecular genetic analysis. The role of phosphorylation is demonstrated by site-directed mutagenesis, and domain liberation is used to study the interaction of WspR with the other components of the signalling pathway. As the overexpression of certain wspR mutant alleles mimics the evolutionary transition from ancestor to niche-specialist, the fitness effects of such overexpression are measured. It is found that some, but not all, wspR alleles do indeed cause adaptation. It is also found that a phenotypically-plastic genotype, with enhanced fitness, can be created by artificial manipulation, but does not occur naturally; this demonstrates the existence of a constraint on evolution. Sequence analysis of independently-isolated WS genotypes shows no evidence of wspR sequence variation, despite its capacity to enhance fitness. A further proteomic and phenotypic characterisation shows variation between ancestral and WS genotypes, and also between different WS genotypes. This demonstrates that there are different mutational routes to the same adaptation.